Prejudice and True Judgement Prejudgment and Final Verdict against 18th Century Traditional Morality. A study of Tom Jones from the Perspective of Gadamer’s Hermeneutics - Shah, Ayaz Muhammad; Shakoor, Abdul (Pakistan Languages and Humanities Review, 2024)
The study analyzes Henry Fielding’s novel, The History of Tom Jones, from the perspective of Gadamer’s hermeneutics. Gadamer states that the reader interprets the text according to his prejudices and preconceived experiences which are the outcome of tradition. Reading the initial parts of the text, the reader projects before himself the meanings of the text as a whole and misunderstands, as these fore-projects, fore-meanings, or presuppositions are his unfounded judgements based on prejudices. Reading the text as a whole, these fore-projects are revised and the reader not only understands his prejudices but the text as well. Reading Tom Jones, the prejudiced reader interprets it according to traditional morality, classical norms and misunderstands the various characters, situations and events. At the end the reader not only comes to understand the text, he also comes to understand himself better as he recognizes his prejudices and prejudgements. He revises his unfounded judgements and gets rid of the prejudices. The research uses the textual analysis method of Gadamer’s hermeneutics to interpret Tom Jones to explore fore-meanings and prejudices. This perspective has been used for the first time to investigate Tom Jones. Thus it opens the door for researchers to probe further in this area.